Heidegger’s “Politics” and the Black Notebooks - Seidel, George (Laval théologique et philosophique, 2017)
Under “politics” is included Heidegger’s entanglement with National Socialism in the early 1930’s, an analysis of his rectoral address, and his resignation as rector. An attempt is made to account for this involvement. Also under “politics” there are Heidegger’s own sketchy, and largely unsuccessful, attempts at forging a philosophy of politics, a couple of which are examined, and critiqued, in detail. There is also a section on Heidegger’s “anti-Semitism,” especially as instanced in the Black Notebooks, which have given rise to considerable controversy of late. An attempt is made to set this in its historical and cultural context. Included also are the many remarks, from the curious to the bizarre, that appear in the Black Notebooks concerning the social and political events of the time between 1931 and 1948. The article closes with what the author sees as the more important themes found in these volumes, which echo themes found in Contributions to Philosophy (From the Event) and in the Unpublished Treatises, part III of the Gesamtausgabe.